Tingginya angka kecacingan pasca pengobatan massal filariasis (DEC dan Albendazole) di SDN Juku Eja Pagatan - Liestiana Indriyati; Annida Annida; Deni Fakhrizal (JHECDs: Journal of Health Epidemiology and Communicable Diseases, 2017)
Helminthiasis considered as "neglected diseases" because it doesn’t induce mortality, but impact on the human resources that can lead to "lost generation. The results of the study in 2008, found the prevalence of worm infection in SDN Juku Eja > 50% where the study was conducted at 3 months post-mass drug administration in it. Required periodic inspections to determine the update status of worm infection in SDN Juku Eja. Descriptive study with cross sectional design was held in SDN Juku Eja Pagatan Kusan Hilir subdistrict in February 2016 (four months after mass drug administration of filariasis in Tanah Bumbu. Population and sample were all students (grades 1-6) SDN Juku Eja Pagatan. 170 pots were distributed, 123 stool samples collected and examined using direct/native method, 102 positive samples (82.93%) consists of Ascaris lumbricoides, Trichuris trichiura, Hookworm, Hymenolepis nana, Hymenolepis diminuta and Enterobius vermicularis. The high prevalence of helminthiasis in SDN Juku Eja riddling civil disobedience in consuming filariasis mass drug or albendazole dose is not able to heal helminthiasis due to the high intensity of helminthiasis. It is estimated that the high prevalence of helminthiasis at the Juku Eja village and the process of infection in the majority of the village so that the program intervention, preventive and promotional of helminthiasis is also need to be implemented at the village level.